Science E-Module Based on Ethnoscience - Paul Telussa, Rivaldo; Tamaela, Kevin Andrea (International Journal of Elementary Education, 2023)
Covid-19 has become an obstacle to the learning process in schools, impacting the availability of teaching materials used. Teachers are challenged to produce engaging and easily understandable electronic teaching materials that can integrate ethnoscience. This research aims to develop and test the feasibility of ethnoscience-based science e-modules. The research method used is Research & Development (R&D) with the Borg & Gall revised Sugiono model, which has been modified into 10 stages. The subjects in this study are content experts (2 people), media experts (1 person), and module testing on third-grade students at elementary school (5 people). Data collection methods used in this research are interviews and observations. Data analysis methods used in this research are descriptive statistics and qualitative analysis. The results of the research and development show that the developed ethnoscience-based science e-module is highly qualified, with an average product result reaching 98.07%, making it suitable for use. The implication of having ethnoscience-based science e-modules is that teachers can deliver learning more easily and understand the culture around them that is studied scientifically.